STRATEGIES IN BUILDING A COLLABORATIVE WORK CULTURE WITH A MODERN MANAGEMENT APPROACH - Mujiburrahman, Mujiburrahman (International Journal Multidisciplinary (IJMI), 2025)
Objective: The research aims to analyze how the simultaneous implementation of innovation, data-driven strategies, and digital transformation can foster a strong collaborative work culture. It highlights the role of modern management approaches in ensuring organizational competitiveness, adaptability, and a results-oriented focus in the contemporary business environment. Method: This study adopts a library research method, utilizing secondary data from scientific journal articles and previous research reports. These sources provide the basis for analyzing the integration of innovation, data, and technology with modern management practices. Results: The findings indicate that innovation-based strategies, when combined with modern management approaches, enhance creativity and cross-functional collaboration, embedding innovation into the core of the organization's culture. Data-driven strategies support clarity in decision-making, transparency in performance evaluation, and conflict-free collaboration, leading to measurable and efficient teamwork. Digital transformation strategies, through the adoption of modern technologies such as collaboration software, cloud computing, and AI, enable increased efficiency, connectivity, and accelerated teamwork across different locations. Novelty: This study offers a comprehensive perspective on the integration of innovation, data, and digital transformation with modern management approaches. It emphasizes how this combination can create an adaptive, cohesive, and competitive organizational culture, providing valuable insights for organizations navigating the challenges of technological and managerial evolution.